Regulatory reforms to increase women micro-entrepreneurs participation in e-commerce - Alifah Dina; Thomas Dewaranu (Center for Indonesian Policy Studies (CIPS), 2022)
The Indonesian entrepreneurial landscape is dominated by micro-enterprises (MIEs), most of which operate informally with a high proportion of women as owners and/or workers. The digital economy can benefit Indonesian women's micro-enterprises (MIEs) by reducing market entry barriers and streamlining the supply chain. However, the traditional norms and regulations are still non-supporting for women's MIEs. This paper proposes three reforms to foster and make sustainable female-owned MIEs through the digital boom.
Keywords: 330; Unternehmerinnen; Kleinstunternehmen; Online-Handel; Indonesien